1973
DOI: 10.5134/175772
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation as an Index of Growth in Corals; Incorporation of ^3h-Thymidine

Abstract: Preliminary experiments are described which are designed to quantify the rates of DNA synthesis in corals. Whole colonies or small sections of Pocillopora damicornis and other corals were incubated in up to 1 ,uCi 3 H-thymidine/ml sea water under field and laboratory conditions. The tissue was extracted with hot 2N NaOH and solubilized, and the 3 H-DNA activity was measured with a liquid scintillation spectrometer. Activity was expressed as CPM/mg dry or wet weight or CPM/calice. Specificity and site of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However Hale (1964), described cell division primarily among the ectodermal cells in the stolons of another hydroid, Clytia. Cheney (1973) used tritiated thymidine to label proliferating cells and found labeled cells primarily among cells of the column epidermis (ectoderm) and of the polyps and coenosarc of the reef coral Pocillopora damicornis. The internal tissues incorporated little, if any, label.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However Hale (1964), described cell division primarily among the ectodermal cells in the stolons of another hydroid, Clytia. Cheney (1973) used tritiated thymidine to label proliferating cells and found labeled cells primarily among cells of the column epidermis (ectoderm) and of the polyps and coenosarc of the reef coral Pocillopora damicornis. The internal tissues incorporated little, if any, label.…”
Section: Discussionmentioning
confidence: 99%
“…Site and frequency of cell division have been investigated in other cnidarians, e.g.. Hydra spp. (David and Campbell, 1972;Neckelmann, 1982); colonial hydroids (Hale, 1964;Campbell, 1968); anemones (Singer, 1971;Minasian 1980); and scleractinian corals (Cheney 1973). Some authors reported that cell proliferation occurs only or at least primarily in the ectoderm (Hale, 1964;Singer, 1971;Cheney, 1973) while others stated that cell division occurs in both the endoderm and the ectoderm (Campbell, 1968;David and Campbell, 1972;Minasian, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation